TEACHING ENGLISH THROUGH DISCOURSE ANALYSIS: A PRACTICE-BASED APPROACH FOR MULTILINGUAL CLASSROOMS - Dr. Saba Khatoon (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Discourse Analysis (DA) studies the structure and language expression in context. It shows how language works and how meaning is created in the given social contexts. It is one of the qualitative research methods with which one can understand how language functions in varied situations. In Discourse Analysis, one does not focus on smaller units of language, such as sounds, words or phrases, rather larger chunks of language, in the form of an entire conversation, text, or collections of texts is studied. This paper explores an innovative pedagogical approach to teaching English to Urdu-medium B.Ed. students through discourse analysis method. Researcher has used texts (discourses) from Class IX & X CBSE text books and News Paper Clippings. The method involved critical reading, understanding language patterns and comprehending sociocultural context for each given text. Students created a portfolio to structure their thoughts and interpretations by engaging with texts through reading, reflection, and discourse analysis. This study highlights how discourse analysis helps in enhancing language proficiency further fostering critical thinking, literary appreciation and cross-linguistic awareness. Conclusions were drawn on classroom experiences and student outputs. The paper explores teaching strategies, assessment practices, and student reflections, offering insights for language teachers in multilingual contexts.